2021
DOI: 10.1051/0004-6361/202040077
|View full text |Cite
|
Sign up to set email alerts
|

Fast methods for tracking grain coagulation and ionization

Abstract: Dust grains play a major role in many astrophysical contexts. They affect the chemical, magnetic, dynamical, and optical properties of their environment, from galaxies down to the interstellar medium, star-forming regions, and protoplanetary disks. Their coagulation leads to shifts in their size distribution and ultimately to the formation of planets. However, although the coagulation process is reasonably uncomplicated to numerically implement by itself, it is difficult to couple it with multidimensional hydr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 87 publications
1
38
0
Order By: Relevance
“…Recently, Marchand et al (2021) proposed a similar method that also can be used to calculate magnetic resistivity analytically. Our numerical tests showed that our method seems to be more robust and applicable over a wide parameter range (e.g., when the dust grains are highly depleted).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Marchand et al (2021) proposed a similar method that also can be used to calculate magnetic resistivity analytically. Our numerical tests showed that our method seems to be more robust and applicable over a wide parameter range (e.g., when the dust grains are highly depleted).…”
Section: Discussionmentioning
confidence: 99%
“…When we implemented and tested their algorithm, we found that it did not converge in the limit where the total dust charge goes to zero. This is because their method uses ψ as the basic variable and use equations (A.3) and (A.4) of Marchand et al (2021) to determine ò and n i . However, their equation (A.4) becomes singular when ò = 1 and á ñ = Z 0 ¯, i.e., gas-phase recombination determines the ionization state.…”
Section: Discussionmentioning
confidence: 99%
“…Applying n M /n e ≈ 107 (Marchand et al 2021) and σ coll w M ≈ 2.4 × 10 −9 (cm 3 s −1 )C s (km s −1 ) 0.6 ≈ 9.1 10 −10 (Pinto & Galli 2008), we obtain k ≈ 5.2 × 10 13 cm −3 G −1 , which is not far from the value measured directly from simulations.…”
Section: Appendixmentioning
confidence: 58%
“…where number density ratio between ions and electrons n M /n e ≈ 107 is applied (Marchand et al 2021). Since the Hall effect drifts the magnetic field outward, the equilibrium radius shrinks as the local value of B z decreases.…”
Section: Weak Field High Rotation Casementioning
confidence: 99%
“…We detail an extension of the ionization model of Marchand et al (2021) to include the thermal ionization of one gas species. It is possible to increase the number of ionized species by adding their contribution in the same manner, at the price of a higher numerical cost.…”
Section: Discussionmentioning
confidence: 99%